Correction to: Evaluation of the mortality registry in Ecuador (2001-2013) - social and geographical inequalities in completeness and quality - Andrés Peralta; Joan Benach; Carme Borrell; Verónica Espinel-Flores; Lucinda Cash-Gibson; Bernardo L. Queiroz; Marc Marí-Dell'Olmo (BMC, 2019)
Following the publication of this article [1], the authors reported a typesetting error in Table 1 that caused the columns of the table to be ordered incorrectly, and a typographical error in a sentence in the Conclusions section.